Komitmen Organisasi, Motivasi Kerja dan Peran Manajer Pengelolaan Keuangan Daerah terhadap Kinerja Manajerial Satuan Kerja Perangkat Daerah di Kabupaten Magelang - Muji Mranani; Intan Dwi Karyati (Jurnal Maksipreneur, 2012)
This aim of this research to suggest organization, motivation, and role of manager financial to performance managerial. The hypothesis of this research is that whether organization commitment, motivation and role of manager financial management positively affect and significant on the local government performance. Collecting data using primary data collection, is the questionnaire by using purposive sampling technique. Data obtained from manajer and used budgeting who work in Magelang District Government with number of questionnaires returns 119 respondents. Methods for analyzing the data using regression. The result of this study suggest organization commitment, motivation and role of manager financial management influence effect have a positive and significant performance managerial. This research is only a qualitative measure performance based on employee perceptions.